EXTRACTION AND ACTIVITIES OF CRUDE PROTEASES FROM SOLID STATE FERMENTATION OF Aspergillus nigeR GROWN ON VARIOUS AGRO WASTE - JAFARU KAMARA, MURJANATU; MOLTONG YILWA, VICTORIA; GODWIN BRIAN, ONWUMERE; rj, MUHAMMED; r, AUSTINE (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Agro-industrial residues are generally considered the best substrates for the solid-state fermentation process. Food processing wastes such as shells of nuts and eggs in Nigeria are usually disposed in dumpsites or are incinerated, causing environmental pollution. This study extracted, estimated and compared enzyme activities from Aspergillus niger under solid-state fermentation (SSF) by utilizing Ground nut shell (GS), Bambara nut shell(BS), Guinea fowl egg shell(GFS) and Layer egg shells (LES) powder as solid substrates. The Agro wastes were dried under the sunlight for four days, ground using a laboratory pestle and mortar separately and sieved to obtain fine powder. The powder was sterilized, supplemented with sodium acetate buffer and pure casein, inoculated with the fungi then left to ferment for six days. The crude extract of the substrates were obtained by filtration and centrifugation. The extracts were assayed for enzyme activity using Sigma Aldrich’s method of assay. The result obtained from the assay demonstrated that proteases were active in all the extracts. However, there was significant difference (P < 0.05) in protease activities in the samples studied. The result revealed that BS and LES showed the highest enzymatic activities (0.797± 0.035 μ/ml), (0.788 ± 0.028 μ/ml), (0.574 ± 0.032 μ/ml), (0.590± 0.040 μ/ml) at 0.2, 0.4, 0.6 and 0.8ml of the crude enzyme extract volume concentrations respectively followed by GS which had the enzymatic activities (0 .456 ± 0.001 μ/ml), (0.391 ± 0.003 μ/ml), (0.335 ± 0.003 μ/ml), (0.205± 0.032 μ/ml) at the volume extract volume concentrations of 0.2, 0.4, 0.6, 0.8ml respectively, meanwhile guinea fowl egg shell had the least enzymatic activities (0.401± 0.028 μ/ml), (0 .336 ± 0.047 μ/ml), (0.250 ± 0.018 μ/ml), (0.255 ± 0.010 μ/ml) at the volume of crude enzyme extract of 0.2, 0.4, 0.6, 0.8ml respectively. In all the shells the highest proteases activities were recorded at 0.2ml of the crude extract volume concentration and the least proteases activities were recorded at 0.8ml of the crude extract volume concentration. This study has proven that proteases were extracted and active from solid state fermentation of Aspergillus niger grown on various agro waste, Therefore proper utilization of these agro-wastes in industrial and scientific settings will not only serve as means of polluted environmental remediation but also as an iualternative to commercially available substrates for microbial growth.